Respon Mahasiswa terhadap Pembelajaran Filsafat Sains Berbasis Studi Kasus dalam Mengembangkan Pemahaman Konsep Ontologi, Epistemologi, dan Aksiologi - Arif, Rifda Nur Hikmahwati (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2025)
This study aims to describe student perceptions of case study-based philosophy of science learning in developing understanding of the concepts of ontology, epistemology, and axiology. The research method used was a descriptive survey with a Likert scale questionnaire instrument distributed to students participating in the Philosophy of Science course in 3 classes (Regular A, Regular B, ICP). The data were analyzed descriptively by calculating the percentage and average of student responses on each indicator. Qualitative analysis was carried out on open answers based on students' impressions and messages. The results showed that the majority of students gave positive responses, with the percentage of “agree” and “strongly agree” answers reaching 92.12%, while the neutral response was 7.28% and the negative response was only 0.60%. Qualitative analysis showed that students were very enthusiastic and felt helped by the varied learning methods and intensive lecturer guidance, although they expected a longer duration of presentations and group discussions to deepen understanding. This finding shows that the case study approach is very acceptable to students and is considered capable of helping them understand the basic concepts of philosophy of science in a more applicable manner. This research is descriptive in nature so it has not been able to test the effectiveness directly, so further research with an experimental design is recommended.